The role of political influence in shaping national energy policy and environmental sustainability - Ricky Ardian Sikumbang; Nabila Husna (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Indonesia's efforts to transition to low-carbon energy are one part of rescaling environmental governance through a process of decentralization, and many actors at the governance level are involved in the transition to low-carbon energy. This research discusses the direction of energy supply policy in Indonesia in the future and its relationship with interested parties, especially the central government. Methods: This study uses literature study and document analysis with stakeholder mapping and PESTEL analysis to examine the energy transition policy in Indonesia, especially the electricity sector. The main focus is on the political aspect by considering economic, social, technological, environmental, and legal factors. Findings: The results show that regulatory and institutional areas have been restricted during the energy plan-making process, all centralized under central government control making it impossible for local action to take place. However, how sub-national actors can harness this space is influenced by many variables, such as political-economic structures, public participation, and power relations. Conclusion: It can increase understanding of the energy transition at every level and offer useful policy advice to engage all interested parties at national and local levels. The openness of the energy transition should be reformed and reduced from the non-substantial political influence for the matter of all Indonesian people. Novelty/Originality of this article: This study provides a unique perspective on Indonesia's energy transition by critically examining the role of governance decentralization in shaping policy directions. Unlike previous studies that focus solely on technological or economic aspects, this research integrates political, social, and environmental dimensions through stakeholder mapping and PESTEL analysis.